PERSPEKTIF EKONOMI POLITIK MEDIA D’ACADEMY INDOSIAR - Parapat, Nelson Halong (Istek Widuri Jakarta, 2017)
This paper describes the problem of media political economic in the field of mass communication. The study of the media political economic is one of the studies of communication based on critical thinking about the mass media which views the media as a channel in the process of commodity exchange in the free market in relation to the use of political factors and power in order to compete and give satisfaction to the audience.The D 'Academy (DA) Indosiar broadcast program is thought to be Indosiar's flagship broadcast program in improving the broadcasting rating, so that the political dimension of broadcasting is directed to create support for the implementation of this broadcast program. The political-economic-media perspective sees that, through the broadcast program D 'Academy there has been so-called commodification. Commodification relates to how the process of transforming goods and services along with their useful value becomes a commodity with exchange rate in the market.The commodification of D'Academy Indosiar has changed the dangdut perspective that was originally a product of indigenous Indonesian traditional culture into a commercial culture product that has the potential to generate profits by working professionally in the working world of the television media industry.